TREATMENT TACTICS FOR PATIENTS WITH DISTAL HUMERUS FRACTURE - Tilyakov Aziz Burievich; Pardaev Saidkosim Norkulovich; Nazarov Sarboz Parda ugli; Umarov Abdullo Suleymanovich (Scholar Express Journals, 2022)
Fractures of the distal humerus are relatively rare injuries in adults with an incidence of 5.7 per 100,000 adults per year. However, transjoint humeral fractures sometimes occur secondary to low-energy trauma (e.g., falls) in elderly patients with osteoporosis of the bone. Transjoint fractures of the humerus have a small contact area with the fracture surface and are prone to rotation of the distal bone fragment, thus surgical intervention is indicated in most cases to provide early postoperative mobilization and restoration of pain-free and satisfactory function of the elbow joint. Although various surgical procedures have been proposed, biomechanical studies show that two plate osteosynthesis or single plate osteosynthesis complements the medial screw to provide adequate fracture stabilization.
Keywords: Distal Humerus Fractures; Early Postoperative Mobilization; fractures; postoperative